Efektifitas Pendidikan Kesehatan dengan Menggunakan Media Booklet terhadap Tingkat Pengetahuan Ibu tentang Stunting - Etik Lusiani; Irine Yunila Prastyawati; Adventia Nobita (Jurnal Ilmu Keperawatan Jiwa, 2021)
Stunting is a chronic malnutrition condition in the first thousand days of life that can cause growth and cognitive development disorders. Stunted growth symptoms are seen after a 2-year-old baby is characterized by below-average or short height. One of the efforts to improve stunting can be made by increasing knowledge about balanced nutrition. The factor of the mother's lack of knowledge about stunting can affect the nutritional status of children under five years of age. The objective of the research was to identify the effect of health education through brochures on the level of knowledge about stunting. This research used a pre-experimental and analytical design with a one-group pre-test and post-test design that was conducted in November 2020 at Bhumi Jati Permai Benjeng Gresik. The number of samples of 30 respondents using the simple random sampling technique. Data collection through questionnaire and statistical tests with Wilcoxon. The results of the study found that after the intervention the respondents had good knowledge of 93%, sufficient knowledge of 7%. The Wilcoxon test shows the value of p = 0.000, so there is an effect of providing health education with brochures on the level of knowledge of mothers about stunting.